Neuroprotective effects of repetitive transcranial magnetic stimulation on Alzheimer's disease: Undetermined therapeutic protocols and mechanisms - Yang Zhu; Lingyi Liao; Shihao Gao; Yong Tao; Hao Huang; Xiangqin Fang; Changyan Yuan; Changyue Gao (Neuroprotection)
Abstract Alzheimer's disease (AD) is a prevalent neurodegenerative disorder characterized by gradual deterioration of cognitive functions, for which an effective treatment is currently unavailable. Repetitive transcranial magnetic stimulation (rTMS), a well‐established noninvasive brain stimulation method, is utilized in clinical settings to address various neuropsychiatric conditions, such as depression, neuropathic pain, and poststroke dysfunction. Increasing evidence suggests that rTMS may enhance cognitive abilities in individuals with AD. However, its optimal therapeutic protocols and precise mechanisms are currently unknown, impeding its clinical implementation. In the present review, we aimed to summarize and discuss the efficacy‐related parameters in rTMS treatment, encompassing stimulus frequency, stimulus pattern, stimulus intensity, and the configuration of the stimulus coil. Furthermore, we reviewed promising rTMS therapeutic protocols involving various combinations of these factors, that were examined in clinical studies. Based on our analysis, we propose that a multisite high‐frequency rTMS (HF‐rTMS) regimen has value in AD therapy, and that promising single‐site protocols, such as HF‐rTMS, applied over the left dorsolateral prefrontal cortex, precuneus, or cerebellum are required to be validated in larger clinical studies. Lastly, we provide a comprehensive review of the potential mechanisms underlying the neuroprotective effects of rTMS on cognition in AD in terms of brain network modulation as well as cellular and molecular reactions. In conclusion, the interaction of diverse mechanisms may be responsible for the total therapeutic effect of rTMS on AD. This review provides theoretical and practical evidence for the future clinical application and scientific research of rTMS in AD.